1996
DOI: 10.1152/jn.1996.75.1.454
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography study of voluntary saccadic eye movements and spatial working memory

Abstract: 1. The purpose of this study is to define the cortical regions that subserve voluntary saccadic eye movements and spatial working memory in humans. 2. Regional cerebral blood flow (rCBF) during performance of oculomotor tasks was measured with [15O]-H2O positron emission tomography (PET). Eleven well-trained, healthy young adults performed the following tasks: visual fixation, visually guided saccades, antisaccades (a task in which subjects made saccades away from rather than toward peripheral targets), and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
302
5
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(366 citation statements)
references
References 46 publications
56
302
5
3
Order By: Relevance
“…This spatial working memory task has been used extensively in studies of monkeys (Funahashi et al, 1989;Sawaguchi and Iba, 2001) and humans (Sweeney et al, 1996), Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…This spatial working memory task has been used extensively in studies of monkeys (Funahashi et al, 1989;Sawaguchi and Iba, 2001) and humans (Sweeney et al, 1996), Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous functional imaging studies have investigated brain activation related to reXexive or voluntary saccades separately. PET studies have shown activation during reXexive saccades in FEF (Anderson et al 1994;Sweeney et al 1996), PEF (Anderson et al 1994), cerebellum, striate cortex and posterior temporal cortex (Sweeney et al 1996). fMRI studies have also shown activation in FEF (Petit et al 1997;Luna et al 1998;Muri et al 1998; Berman et al Table 2 Areas of activation (voluntary saccades > Wxation) with cluster size, maximum t value within the cluster, MNI coordinates of the maximum t value, anatomic labels, percentage of cluster size and functional area All areas were thresholded at P < 0.05 with FDR (whole brain study) or at cluster level (P < 0.05) corrected for multiple comparisons (cerebellum study) and with a minimum cluster size of 10 voxels L left hemisphere, R right hemisphere, FEF frontal eye Welds, PEF parietal eye Welds, MT/V5 motion-sensitive area (MT/V5), PVA/V1 primary visual areas (V1) a The unassigned areas for each cluster are not listed in the Muri et al 1998;Berman et al 1999;Nobre et al 2000), and the cerebellum (Nobre et al 2000), as well as in SEF (Luna et al 1998;Berman et al 1999), the precuneus , the cingulate gyrus Nobre et al 2000), MT/V5, PVA/V1 and the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…Functional imaging studies have shown that the precuneus is involved in reXexive saccadic eye movements and is associated with shifts of spatial attention (Cavanna and Trimble 2006). The anterior cingulate gyrus is involved in target detection (Posner and Petersen 1990) and is activated during self-paced saccades (Paus et al 1993;Petit et al 1996;Sweeney et al 1996) and during reXexive saccades Mort et al 2003). Neurons in the posterior cingulate cortex of primates Wre instantly to assign the spatial coordinates after a saccade in which the eye position signals are provided and to permit monitoring of either eye or self motion (Olson et al 1996).…”
Section: Precuneus Cingulate Gyrus and Angular Gyrusmentioning
confidence: 99%
“…Imaging studies (Sweeney et a!., 1996) have shown thal the frontal cortex is not strongly activated unless the task at hand requires its unique abilities, such as in memory-guided saccadcs or anti-saccades. Taken together, these data suggest a hierarchy of control, such that visual inputs to the SC dominate by default, but the frontal cortex can assume control of the SC when simple reactive eye movements are insuff-Icient ( Figure I).…”
Section: Introductionmentioning
confidence: 99%